Factors that influenced customer's decision in choosing Hotel Seri Malaysia Malacca / Siti Hajar Abdul Wahab - Abdul Wahab, Siti Hajar (Faculty of Business and Management, 2008)
This research has been conducted for the purpose of "To Study the Factors That Influenced Customer's Decision in Choosing Hotel Seri Malaysia Malacca". In this research, the main problem is the management of the hotel doesn't know the actual factor that influential their customer to come and stay at the hotel. Thus, the main objective of this research is to identify the most influential factor that influences customer decision to stay at Hotel Seri Malaysia Malacca. At the same time, to know either there is significant relationship between customer decision and element of servicescape. The set of questionnaire was distributed to 50 residents or customers of Hotel Seri Malaysia Malacca. This research use convenience sampling and descriptive statistic in interpret the data such as reliability statistic, frequency analysis, correlation analysis and descriptive analysis. From the finding, the most influential factor is physical facility and each element of servicescape is significant with customer decision.